ĐKXĐ x \neq \frac{4}{7} ; x \neq \sqrt[3]{- 2}\frac{x(x^{2} - 56)}{4 - 7x} - \frac{21x+22}{x^{3} + 2} = 4
<=>(\frac{x(x^2 - 56)}{4 - 7x} )- (\frac{21x+22}{x^{3} + 2} - 1) = 0
<=> (x^{3} - 21x -20)(\frac{1}{4 - 7x} + \frac{1}{x^{3} + 2}) = 0
<=> ( x - 5)(x+4)(x+1) (\frac{1}{4 - 7x} + \frac{1}{x^{3} + 2}) = 0
Xét trường hợp
\frac{1}{4 - 7x} + \frac{1}{x^{3} + 2} = 0
<=> x^3 - 7x + 6 = 0
<=> (x- 2)( x- 1)(x+3)= 0
<=> x = 2 hoặc x= 1 hoặc x = - 3
Xét trường hợp
( x - 5)(x+4)(x+1) = 0
<=> x = 5 hoặc x = - 4 hoặc x = -1
Vậy phương trình đã cho có các nghiệm là x \in {-4 ;-3 ;-1, 1, 2, 5}